ANALISIS YURIDIS ATAS PEMBATALAN PERJANJIAN KERJASAMA EVENT ORGANIZER DENGAN PENGGUNA JASA (STUDI PADA CV.BINTANG MANDIRI IN7 WEDDING ORGANIZER & DECORATION DI MEDAN)ANALISIS YURIDIS ATAS PEMBATALAN PERJANJIAN KERJASAMA EVENT ORGANIZER DENGAN PENGGUNA JAS - SITI AYU REVANI (PREMISE LAW JURNAL, 2015)
The development of legal agreement causes many people to be connected with other people in a certain contract. In a contract, there is a force majeure which is useful for proving whether there is a force majeure or not in the contract. Therefore, the coverage of force majeure is very wide so that the attachment of force majeure in a contract is very useful to prevent the parties concerned from any dispute. In the mutual agreement, the Wedding Organizer explains the definition of compensation when there is a default and failure in a contract done by one of the parties, and how about the provision of compensation when there is a force majeure. The research used judicial normative method. The data were gathered by conducting library research and field research with descriptive analysis approach and analyzed by using qualitative analysis. The mutual agreement used by the Wedding Organizer was unilateral agreement, based on standard agreement. Keywords: Agreement, Force Majeure, Wedding Organizer